Quasi‐Ordered Nanoforests with Hybrid Plasmon Resonances for Broadband Absorption and Photodetection. (19th June 2021) - Li, Mao; Shi, Meng; Wang, Bin; Zhang, Chenchen; Yang, Shuai; Yang, Yudong; Zhou, Na; Guo, Xin; Chen, Dapeng; Li, Shaojuan; Mao, Haiyang; Xiong, Jijun
Abstract: With the continuing development of green energy technology, solar energy is the most widely distributed and easily utilized form of energy in nature. High‐absorption absorbers over a wide spectrum range are beneficial for solar energy harvest. Herein, a fast and efficient method is developed to fabricate a broadband absorber consisting of quasi‐ordered nanoforests and metal nanoparticles using a simple plasma bombardment process on a 4‐inch silicon wafer, offering high throughputs that can meet practical application demands. The absorber exhibits high absorption exceeding 90% from 300 to 2500 nm, good absorption stability with negligible disturbance from the polarization and the incident angle of light. This effective absorption behavior can be ascribed to multilevel hybridization of the plasmon resonances in the hybrid structures and cavity mode resonances inside the nanoforests. Furthermore, the absorber is integrated onto a thermopile for photodetection with largely enhanced photoresponse from 532 to 2200 nm. The photoinduced voltage of the devices shows a large increment of 433% at 100 mW cm −2 light power density, in comparison with a contrast pristine thermopile. It is expected that such a broadband absorber holds great potential for multiple applications, including solar steam generation, photodetection, and solar cells. Abstract : A quasi‐ordered nanoforests‐based absorber with multilevel hybrid resonances is proposed for broadband high absorption. The absorber shows absorption properties independent of polarization and incident angle of light. By integrating the absorber onto a thermopile device, the device achieves large enhancement in photoresponses, providing an application prospect for diverse scenes where effective light absorption is required.